Theology of canon law and Vatican II: the epistemological nature of ecclesial law - Maule, Mari Teresinha (2024)
This article aims to discuss about the aspects of the canonic law, which has its main focus in Vatican II and consequently the epistemological nature of ecclesiastical law. It should be noted that the methodology used was of bibliographic review, for this purpose, research and reading of texts were carried out. As stated in the text, Vatican II did not come about spontaneously, but rather as a result of a series of social, theological and ecclesiastical factors that were preparing the ground until the so-called “ecclesiastical spring”. It adopted a pastoral character and its ecclesiology was formulated based on the dogmatic constitution on the church Lumen gentium and the pastoral constitution on the church in the modern world, Gaudium et spes. In contrast to the merely juridical conception, Vatican II highlights the dimension of mystery (LG I), the Trinity Church, which is born of the Father, is animated by the spirit (LG 4) and reflects the light of Christ (LG 1). It manifests itself as a multitude gathered by the unity of the Father and the Son and the Holy Spirit (LG 4). In an attempt to return to the origins of the biblical and primitive church, it calls the People of God to be present and speaks of community, especially towards the poorest and most marginalized. Being this is the source from which the legal framework of canon law, as well as ecclesiastical law, emanates.